Working capital management, firm performance and nature of business: An empirical evidence from India. Issue 1 (9th March 2020) - Sawarni, Kumar Sanjay; Narayanasamy, Sivasankaran; Ayyalusamy, Kanagaraj
Abstract : Purpose: This paper aims to investigate the impact of the efficiency of working capital management (WCM) on the performance of a sample of Indian companies and explore how the nature of the firm's business influences the significance and direction of this impact. Design/methodology/approach: The data for this study were collected for the period of 2012–2018 for 414 non-financial firms listed on the Bombay Stock exchange. Fixed-effect regression models were run by taking Tobin's Q and return on equity (ROE) as dependent variables, and net trade cycle (NTC) and its components as explanatory variables in the presence of liquidity, leverage, size, age and growth as control variables. Sample firms were segregated into manufacturing, trading and service groups, and regression models were used for all the groups to understand the effect of the nature of a firm's business. Findings: WCM efficiency has a significant impact on the performance of the sample firms. Non-financial Indian firms deliver better financial performance by maintaining lower NTC. Like NTC, its components also impact firm value and profitability. The results report that the significance of the relationship varies depending upon the nature of the firm's business. Originality/value: The previous research studies had not used a sample of large number of Indian firms. Unlike previous studies, this study reports the influence of the nature of business on the relationship between WCM and firm performance. Further, this paper also examines how the individual components of working capital influence the performance of Indian firms.